Localized pmrB hypermutation drives the evolution of colistin heteroresistance - Kapel, N; diaz, J; Maclean, R (Cell Press, 2022)
Colistin has emerged as an important last line of defence for the treatment of infections caused by antibiotic resistant Gram-negative pathogens, but colistin resistance remains poorly understood. Here we investigate the responses of |1,000 populations of an MDR strain of P. aeruginosa to a high dose of colistin. Colistin exposure causes rapid cell death, but some populations eventually recover due to the growth of sub-populations of heteroresistant cells. Heteroresistance is unstable and resistance is rapidly lost under culture in colistin-free medium. The evolution of heteroresistance is primarily driven selection for pre-existing mutations at two hotspot sites in the PmrAB regulatory system. Localized hypermutation of pmrB generates colistin resistance at 103-104 times the background resistance mutation rate(|2x10-5 20 per cell division). PmrAB provides resistance to antimicrobial peptides that are involved in host immunity, suggesting that this pathogen may have evolved a highly mutable pmrB as an adaptation to host immunity.